A Semantic Analysis of Denotative and Connotative Meanings in the Lyrics of “Who Knows” by Daniel Caesar - Zaskia Azatil Isma; T. Thyrhaya Zein; Nasqya Rizsa Fatharani; Dzakiah Qurrota Aini; Putri Ramadhani; Rakha Athallah Widya Dhana (IKRA-ITH ABDIMAS, 2026)
The purpose of this research is to identify and interpret the literal and implied meanings that existed in the "Who Knows” lyrics by Daniel Caesar. This study uses a qualitative descriptive method using an interpretive semantic approach, focusing on denotative and connotative analysis. The data were collected from the official lyrics and analyzed through stages of identification, classification, and interpretation. The findings reveal that while denotative meanings present straightforward descriptions of thoughts and situations, the connotative meanings uncover deeper emotional layers such as uncertainty, self-doubt, hope, and vulnerability in romantic relationships. The study concludes that the song reflects modern relationship dynamics characterized by ambiguity yet sustained by sincere emotional commitment, demonstrating that meaning in lyrics extends beyond literal interpretation.Keyword: Semantics, denotation, connotation, song lyrics, romantic relationships